Modeling of aerial biomass in dry subtropical temperate forests in northeastern Mexico - Bautista Cruz, Angelina; González Cubas, Rigoberto; Treviño Garza, Eduardo Javier; Yerena Yamallel, José Israel; Alanís Rodríguez, Eduardo; Aguirre Calderón, Oscar Alberto (BOSQUE, 2023)
Information regarding biomass and wood volume of trees are two important factors that allow for analysis of the sustainability of forests. The objective of this study was to calculate the aerial biomass, amount of carbon and timber volume of dry subtropical temperate forests containing Pinus pseudostrobus Lindl. in northeastern Mexico. Field data corresponding to 57 sampling sites were used, including 28 Permanent Forest Research Sites and 29 conglomerates from the National Forest and Soil Inventory, from which biomass, carbon and volume were calculated using allometric equations. The spectral data (NDVI, Normalized Difference Vegetation Index) were derived from a Landsat 8 image taken in the year 2020. Using the results of the linear relationship between biomass-carbon and NDVI, a positive correlation (P = 0.007) was found using Spectral data from Landsat images for biomass increase and carbon sequestration in coniferous forests in the state of Nuevo León. The research contributes to the understanding of the dynamics of carbon and biomass for the improvement of sustainable development.